Casting Light on the Micro-Organisms in Digestate: Diversity and Untapped Potential - Ashira Roopnarain; Muyiwa Ajoke Akindolire; Haripriya Rama; Busiswa Ndaba (Fermentation, 2023)
Anaerobic digestion (AD) is an established process for waste conversion to bioenergy. However, for the AD process to be viable, it is imperative that all products be adequately valorized to maximize the benefits associated with the technology and in turn promote economic feasibility and technology uptake. Digestate is a byproduct of the AD process that is oftentimes overshadowed by the primary product, biogas, however the potential of digestate is vast. Digestate is composed of undigested organic matter, inorganic matter, and microorganisms. Whilst digestate has frequently been utilized as a soil amendment due to its abundance of readily available plant nutrients, the microbial content of digestate is oftentimes neglected or undermined. The array of microbes prevalent in digestate may contribute to expanding its potential applications. This microbial composition is shaped by several factors including resident microbial communities in inoculum and feedstock, feedstock composition, temperature of the AD system, AD additives and augmenting agents as well as post-treatment strategies, amongst others. Hence, it is hypothesized that digestate microbial content can be manipulated to target particular downstream applications by altering the above-mentioned factors. In so doing, the value of the produced digestate may be improved, which may even lead to digestate becoming the most lucrative product of the AD process. This review provides a holistic overview of the factors influencing the microbial community structure of digestate, the microorganisms in digestate from diverse AD systems and the associated microbial functionality as well as the potential applications of the digestate from a perspective of the resident microflora. The aim of the paper is to highlight the vast potential of microorganisms in digestate so as to broaden its applicability and value.